Distinguishing the Best from the Rest - Sharma, Basu (Journal of Comparative International Management)

(untitled) (Management Futures, 1999)
This essay examines the notion of "best practices", summarizes key studies on this theme, and discusses methodological concerns related to empirical studies of best management practices.